Insecurity in Old Age: A Comparative Case Study of Social Pension Programs between Indonesia and Malaysia - Pensaengon, Khemarin (Journal of Arts and Thai Studies, 2024)
Objectives: The social pension is considered a welfare program for the elderly that does not require contribution. Studying the policy and implementation of the social pension program in the ASEAN region is intriguing as many countries in the region are entering an aging society. This study focuses on the social pension programs for the elderly, comparing the current situations in Indonesia and Malaysia. It also analyzes the current problems and challenges in implementing social pension in both countries. Methods: This research is a qualitative study utilizing the documentary research method, where the researcher investigates and gathers information from relevant documents. The content scope of this study includes examining the development of elderly welfare policies in the countries of Indonesia and Malaysia. The study covers the period from 1998 to 2022. Results: This study found that there are similar challenges, especially in terms of relatively low coverage, accessibility issues due to the archipelagic geography, and sustainability concerns in project implementation due to reliance on tax-funded budgets when comparing the social pension for the elderly in Indonesia and Malaysia. Additionally, with the continuous increase in the elderly population due to medical advancements coupled with low birth rates, both countries face a labor shortage, impacting the overall economy. This, in turn, affects the sustainability of social pension programs in both countries, leading to insecurities for the elderly population in their post-retirement lives. Application of this study: The findings of this study can be applied to shaping welfare policies for the elderly in ASEAN countries with similar contextual aspects. Furthermore, these findings can be utilized in planning strategies to address the imminent increase in the elderly population in the near future.